Pengembangan Media Informasi dalam Komunikasi Risiko untuk Penanganan dan Pencegahan Covid-19 di Sulawesi Selatan - Riskiyani, Shanti; Zainuddin, Andi Alfian; Nurdin, Nurhaya (Jurnal Kesehatan Manarang, 2022)
WHO introduced Covid-19 as a global health problem on January 30, 2020, and currently here are more than 6.05 million cases of Covid-19 reported from 188 countries and resulted in 368,000 deaths. One of the efforts recommended by the Indonesian Ministry of Health to prevent the spread of this infection is to limit social contact and practice clean and healthy living. This study develops a communication strategy in education on the prevention and handling of COVID-19 in South Sulawesi. Through a qualitative approach, data collection was carried out through focus group discussions to identify a picture of the community's response in dealing with this pandemic. This study resulted in infographics and guides containing information related to the prevention and handling of COVID-19. In addition, voice messages have been developed about 3M's behavior and the correct use of masks. A communication strategy by considering the local situation in the form of community responses is important when conducting education during a pandemic. This is due to the large amount of information spread in the mass media that is easily accessible by the public. In addition, the ever-changing situation also requires us to be able to continue to innovate in developing health messages that will be disseminated to the public. Messages created can include new information, confirmation or refutation of hoaxes that may develop.